2021
DOI: 10.1002/adtp.202100018
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development on Controlled Synthesis of Mn‐Based Nanostructures for Bioimaging and Cancer Therapy

Abstract: Manganese‐based nanomaterials have emerged as potential and important nanomedicine for bioimaging and cancer treatment due to their excellent electronic structure and intrinsic physiochemical property and sensitivity to tumor microenvironment (TME). In this review, the recent progress on the synthesis and applications of various manganese oxides, sulfides with well‐controlled size, morphologies, chemical composition, and nanostructures have been summarized. Numerous samples have been chosen as examples to demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 147 publications
(163 reference statements)
1
10
0
Order By: Relevance
“…The Mn on the surface provides a larger hyperfine coupling constant, while the Mn inside the crystal will decrease the hyperfine coupling constant. The large hyperfine coupling constant of MnSe nanoparticles was similar to that observed for Mn 2+ localized on the surface of Ag 2 Se (93.8 G) . The results implied that a large hyperfine coupling constant of 95.0 G was the result of the greater contribution of Mn 2+ on the surface of MnSe nanoparticles, which might be attributable to the fact that the ultrasmall particle size of MnSe nanoparticles provided the large surface-to-volume ratio. It has been reported that the T 1 relaxation times shortening effect increased as the size of nanoparticles decreased, which was due to the large surface-to-volume ratio and the high-spin Mn 2+ of small size nanoparticles accelerating the interactions with water protons. Besides, dynamic light scattering (DLS) was used to measure the hydrodynamic size of MnSe nanoparticles in water to be 61.82 ± 1.22 nm, as shown in Figure S4a, which was much larger than the size of MnSe crystal (3.50 ± 0.52 nm). At the same time, bicinchoninic acid assay (BCA) was used to quantify the protein concentration on the surface of MnSe nanoparticles, as shown in Figure S4b.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The Mn on the surface provides a larger hyperfine coupling constant, while the Mn inside the crystal will decrease the hyperfine coupling constant. The large hyperfine coupling constant of MnSe nanoparticles was similar to that observed for Mn 2+ localized on the surface of Ag 2 Se (93.8 G) . The results implied that a large hyperfine coupling constant of 95.0 G was the result of the greater contribution of Mn 2+ on the surface of MnSe nanoparticles, which might be attributable to the fact that the ultrasmall particle size of MnSe nanoparticles provided the large surface-to-volume ratio. It has been reported that the T 1 relaxation times shortening effect increased as the size of nanoparticles decreased, which was due to the large surface-to-volume ratio and the high-spin Mn 2+ of small size nanoparticles accelerating the interactions with water protons. Besides, dynamic light scattering (DLS) was used to measure the hydrodynamic size of MnSe nanoparticles in water to be 61.82 ± 1.22 nm, as shown in Figure S4a, which was much larger than the size of MnSe crystal (3.50 ± 0.52 nm). At the same time, bicinchoninic acid assay (BCA) was used to quantify the protein concentration on the surface of MnSe nanoparticles, as shown in Figure S4b.…”
Section: Resultssupporting
confidence: 53%
“…The surface coating increased the nanoparticle size, which might result in slowed dynamics of nanoparticles in solution . However, the hydrophilicity of the surface coating of the nanoparticles was conducive to the water exchange efficiency and a good solvent diffusion state around the surface of the nanoparticles, which in turn affected the T 1 relaxation times. ,, Together, the ultrasmall particle size and hydrophilic coating of MnSe nanoparticles might be the reason for the efficient longitudinal relaxation enhancement of water protons. Compared with other nanostructures as T 1 -MRI CAs, ,, the MnSe nanoparticles have a small particle size and a hydrophilic coating that is naturally carried without further modification.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, inorganic nanomaterials have been primarily created in the past decade, with remarkable progress in recent years. These inorganic nanoplatforms possess inherent electronic, photonic, acoustic, and magnetic properties not possessed by conventional organic nanosystems (Ren et al, 2021; Ruan & Qian, 2021). Among them, copper‐based nanomaterials (Cu‐based NMs) are the most representative example in the field of nanomedicine and have attracted extensive attention, mainly due to their unique physicochemical properties and excellent biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…The development of new positive CAs with all the above-mentioned issues resolved is urgently needed. Over the past 10 years, Mn-based nanomaterials such as Mn x O y and MnS have drawn increasing interest in biomedical applications [ 28 32 ]. These nanoplatforms with passive or active targeting ability are capable of selectively accumulating at the tumor site, which leads to highly effective MR imaging after degradation in the tumor microenvironment (TME) [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%